Novel PAX4 variant in a child and family with diabetes mellitus - case report and review of the literature - Lee, Yee-Lin; Ting, Tzer-Hwu; Lim, Chong-Teik; Arrumugam, Crystal Arthini; Karuppiah, Thilakavathy; Ling, King-Hwa (Walter de Gruyter GmbH, 2023)
Objectives: PAX4 (Paired box 4), a transcription factor crucial in pancreatic beta cell development and function, is a rare cause of maturity-onset diabetes of the young (MODY). What is new? A novel PAX4 variant is verified by family segregation study to be likely pathogenic. A child below 10 years of age diagnosed to have PAX4-MODY, differing from previously reported paediatric cases diagnosed in adolescence. Case presentation: A child with diabetes diagnosed at age 8 years, harbored a PAX4 variant, c.890G>A (p.Gly297Asp), initially classified as variant of uncertain significance. Eleven family members (7 adults and 4 children) with and without diabetes across 3 generations were genotyped. The variant co-segregated with diabetes or prediabetes across 3 generations of the family. The variant is reclassified as likely pathogenic according to standard guidelines. Conclusion: Genetic testing is essential to confirm PAX4-- MODY as the presentation is variable even within the same family. PAX4 mutation needs to be considered in MODY genetic testing in Asian patients.